Kemampuan ROA dan NPM dalam Memengaruhi Return Saham - Melly Fuji Astuti; Zulkarnain Zulkarnain (Institut Manajemen Wiyata Indonesia, 2020)
Return is what investors who invest their capital expect. ROA is used to determine company performance based on the company's ability to utilize its assets, this can lead to appreciation and depreciation of stock prices. NPM calculates the extent to which the company's ability to generate net income at a certain sales level. A high ratio gives confidence to investors to own company shares which can increase stock returns in the future. This study aims to determine: (1) the effect of return on assets (ROA) on stock returns, (2) the effect of net profit margin (NPM) on stock returns, and (3) the effect of return on assets (ROA) and net profit margin ( NPM) on stock returns simultaneously. The research subjects were manufacturing companies in the food and beverage sub-sector on the IDX 2012-2016. The data used are secondary data. The data analysis technique used in this study is Multiple Linear Regression Analysis. The results showed that (1) return on assets (ROA) has no effect on stock returns. (2) net profit margin (NPM) has no effect on stock returns. 3) simultaneous return on assets (ROA) and net profit margin (NPM) has no effect on stock returns.